2020
DOI: 10.3389/fphar.2020.566638
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Tacrolimus Trough Concentrations During the First Year After Kidney Transplantation: A National Retrospective Cohort Study

Abstract: Background: There is a lack of data in the literature on the evaluation of tacrolimus (TAC) dosage regimen and monitoring after kidney transplantation (KT) in Kuwait. The aim of the present study was to evaluate TAC dosing in relation to the hospital protocol, the achievement of target TAC trough concentration (C0), the prevalence of TAC side effects (SEs), namely, posttransplant diabetes mellitus (PTDM), denovo hypertension (HTN), and dyslipidemia, and factors associated with the occurrence of these SEs among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Tacrolimus-induced PTDM may involve various changes through different mechanisms, including decreased insulin secretion, increased insulin resistance and increased insulin resistance β changes in cell function and peripheral insulin resistance ( Dai et al, 2020 ). A previous study indicated that higher tacrolimus concentration was closely associated with PTDM ( Alghanem et al, 2020 ). It has been reported that tacrolimus concentration > 15–20 ng/mL within the first month post-transplantation was an important risk factor for PTDM ( Ajabnoor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus-induced PTDM may involve various changes through different mechanisms, including decreased insulin secretion, increased insulin resistance and increased insulin resistance β changes in cell function and peripheral insulin resistance ( Dai et al, 2020 ). A previous study indicated that higher tacrolimus concentration was closely associated with PTDM ( Alghanem et al, 2020 ). It has been reported that tacrolimus concentration > 15–20 ng/mL within the first month post-transplantation was an important risk factor for PTDM ( Ajabnoor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole inhibits CYP3A4 and P-glycoprotein, resulting in increased tacrolimus concentrations, which increases the potential for adverse effects because of excessive immunosuppression and toxicity (e.g., nephrotoxicity and neurotoxicity) [ 13 , 14 ]. Tacrolimus trough concentrations should be assessed upon the initiation of itraconazole and subsequent dose adjustments to ensure that concentrations are within the narrow therapeutic window [ 15 , 16 ]. Notably, itraconazole oral formulations (e.g., solution, capsule, and tablet) have inherent PK differences and should not be used interchangeably [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows the detailed validation results and the missing parameter data of other neutral drugs. Most neutral drugs that underwent a validation study have an LLOQ concentration below the plasma/serum concentration range of their drugs, except for everolimus, perampanel, and sirolimus [ 16 , 53 , 61 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. Everolimus has an LLOQ of 0.02 µg/mL [ 61 ], whereas its concentration range is 0.003–0.008 µg/mL [ 100 ].…”
Section: Analytical Validation Of Volumetric Absorptive Microsampling...mentioning
confidence: 99%